Chronic nicotine impairs the angiogenic capacity of human induced pluripotent stem cell-derived endothelial cells in a murine model of peripheral arterial disease - Alex H.P. Chan, PhD; Caroline Hu, BS; Gladys C.F. Chiang, BS; Chisomaga Ekweume, BS; Ngan F. Huang, PhD (JVS - Vascular Science, 2023)
Objective: Lifestyle choices such as tobacco and e-cigarette use are a risk factor for peripheral arterial disease (PAD) and may influence therapeutic outcomes. The effect of chronic nicotine exposure on the angiogenic capacity of human induced pluripotent stem cell-derived endothelial cells (iPSC-ECs) was assessed in a murine model of PAD. Methods: Mice were exposed to nicotine or phosphate-buffered saline (PBS) for 28 days, followed by induction of limb ischemia and iPSC-EC transplantation. Cells were injected into the ischemic limb immediately after induction of hindlimb ischemia and again 7 days later. Limb perfusion was assessed by laser Doppler spectroscopy, and transplant cell survival was monitored for 14 days afterward using bioluminescence imaging, followed by histological analysis of angiogenesis. Results: Transplant cell retention progressively decreased over time after implantation based on bioluminescence imaging, and there were no significant differences in cell survival between mice with chronic exposure to nicotine or PBS. However, compared with mice without nicotine exposure, mice with prior nicotine exposure had had an impaired therapeutic response to iPSC-EC therapy based on decreased vascular perfusion recovery. Mice with nicotine exposure, followed by cell transplantation, had significantly lower mean perfusion ratio after 14 days (0.47 ± 0.07) compared with mice undergoing cell transplantation without prior nicotine exposure (0.79 ± 0.11). This finding was further supported by histological analysis of capillary density, in which animals with prior nicotine exposure had a lower capillary density (45.9 ± 4.7 per mm2) compared with mice without nicotine exposure (66.5 ± 8.1 per mm2). Importantly, the ischemic limbs mice exposed to nicotine without cell therapy also showed significant impairment in perfusion recovery after 14 days, compared with mice that received PBS + iPSC-EC treatment. This result suggested that mice without chronic nicotine exposure could respond to iPSC-EC implantation into the ischemic limb by inducing perfusion recovery, whereas mice with chronic nicotine exposure did not respond to iPSC-EC therapy. Conclusions: Together, these findings show that chronic nicotine exposure adversely affects the ability of iPSC-EC therapy to promote vascular perfusion recovery and angiogenesis in a murine PAD model. : Clinical Relevance: Cell therapy is a promising approach to induce revascularization in ischemic tissues associated with PAD. However, the role of lifestyle choices in modulating the efficacy of cell therapy is largely unknown. Using a murine model of PAD, this work demonstrates that chronic nicotine exposure can impair the ability of cell therapy to exert a therapeutic benefit. These results have important implications in the design of treatment options for patients with PAD with a history of tobacco or e-cigarette use.